Buzz Group Technique to Promote Students Reading Comprehension - Afifah, Nurul (Universitas PGRI Semarang, 2019)
This present study was quasi experiment research. This study aimed to find out whether or not there is any the improvement of the students? reading comprehension by using buzz group technique. The population of the study was all the eighth grade students of SMP SENTOSA BAKTI BATURAJA in Academic Year 2019/ 2020. The sample was taken by using cluster random sampling. The sample is divided by two experimental class and control group. The try-out was done at VIII. C with 22 respondents. The data was collected by using test. The reliability of the data was taken through Alpha Cronbach. The data were analyzed by using paired T-test of control class and paired t-test of experimental class and independent t-test too. The result showed that from the mean score was 71 improved to be 84, 6 and based on independent T-test the value of T obtained was 8,122 as significant level of 0.05 for 2 tailed testing and degree of freedom (df) was 48 the critical value of T table 3, 425. The value was higher than T table (8,122>3,425) and the value sig, (2 tailed)= 0.000 less than the value of significant level (0.05). It mean that there was significant improvement the students who was taught by using buzz group technique and those who was not at SMP SENTOSA BAKTI Baturaja. It concluded that Buzz group technique was effective to promote students? reading comprehension at the Eighth Grade students of SMP SENTOSA BAKTI BATURAJA.